1974
DOI: 10.1128/aem.28.1.31-34.1974
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Ochratoxin A and Citrinin During Malting and Brewing Experiments

Abstract: The fate of ochratoxin A and citrinin during malting and brewing processes was studied by the use of naturally contaminated lots of barley, as well as by the addition of crystalline toxins to the mash. Complete degradation was observed for ochratoxin A from moderately contaminated barley lots and for citrinin added to mash. The use of highly contaminated barley resulted in transmission of ochratoxin A into the beer, but only 2 to 7% of the initial content was detected, corresponding to levels of 6 to 20 jg of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Penicillium spp., particularly Penicillium verrucosum is OTA producer as well (Pitt 1987). OTA is a derivative of isocoumarin linked to l-phenylalanine and it has a potent nephrotoxic (Krogh et al 1974;Mortensen et al 1983), teratogenic (Arora and Fröelén 1981), genotoxic (Dirheimer 1998), immunosuppressive (Haubeck et al 1981) and carcinogenic (Boorman 1989) properties. If the consumers take moderate to low concentrations of this mycotoxin in the long term, much more serious problem may arise.…”
Section: Introductionmentioning
confidence: 99%
“…Penicillium spp., particularly Penicillium verrucosum is OTA producer as well (Pitt 1987). OTA is a derivative of isocoumarin linked to l-phenylalanine and it has a potent nephrotoxic (Krogh et al 1974;Mortensen et al 1983), teratogenic (Arora and Fröelén 1981), genotoxic (Dirheimer 1998), immunosuppressive (Haubeck et al 1981) and carcinogenic (Boorman 1989) properties. If the consumers take moderate to low concentrations of this mycotoxin in the long term, much more serious problem may arise.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of the occurrence of ochratoxin A in different cereals have been carried out in most parts of the world [Krogh, 19871. In the Scandinavian countries Krogh et al [1973Krogh et al [ , 1974b and Pedersen and Hansen [ 198 11 surveyed the situation in Denmark, while different studies have been carried out by Krogh et al [1974a], Akerstrand and Josefsson [1979], and Hokby et al [1979] in Sweden and Olberg and Yndestad [I9821 in Norway. Hult et al [1979, 19801 have shown that plasma samples from slaughtered pigs can be used to evaluate the ochratoxin A content of the pork meat and the feed consumed by the pigs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the in vitro ‐generated concentration range (≤100 ug/L) was representative of the highest concentration likely to be found in processed beer. This is because barley grain is stored under conditions that do not promote the growth of moulds and heavily contaminated grains are demonstrated to fail to germinate during malting . Generally, OTA contents in barley, malted barley and beer brewed from them are up to 12, 6.6 and 0.5 μg/L, respectively .…”
Section: Resultsmentioning
confidence: 99%